Administrative territorial structures in EU countries and their specifics - Halásková, Martina; Halásková, Renáta (Univerzita Pardubice, 2009)
The article is focused on administrative territorial structures in European Union countries and their specifics. Each state must respect its internal, territorial and other conditions and in connection to that, create its own system of organization of these relations. Attention is given to the structure of public administration in EU countries, administrative territorial division, differences and identical characteristics, local specifics and structure and differences according to NUTS regions in EU.
Keywords: Public Administration; European Union; administrative territorial structures; local administration; Local government; specifics of organization; territorial units; NUTS regions